Clinical Applications of Biomaterials : State-of-the-Art Progress, Trends, and Novel Approaches - Kaur, Gurbinder (Springer International Publishing : Imprint: Springer, 2017)
This book examines the most novel and state-of-the-art applications of biomaterials, with chapters that exemplify approaches with targeted drug delivery, diabetes, neurodegenerative diseases and cranioplasty implants. Expert contributors analyze biomaterials such as calcium phosphate, sol-gel and quenched glasses, metallic and polymer implants, bioactive glass, and polymer composites while also covering important areas such as the soft tissue replacement, apatites, bone regeneration and cell encapsulation. This book is appropriate for biomedical engineers, materials scientists, and clinicians who are seeking to implement the most advanced approaches and technologies with their patients.
Keywords: Materials science.; Biomedical engineering.; Biomaterials.; elektronické knihy; electronic books